If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 10x + -27 = 7x + 54 Reorder the terms: -27 + 10x = 7x + 54 Reorder the terms: -27 + 10x = 54 + 7x Solving -27 + 10x = 54 + 7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-7x' to each side of the equation. -27 + 10x + -7x = 54 + 7x + -7x Combine like terms: 10x + -7x = 3x -27 + 3x = 54 + 7x + -7x Combine like terms: 7x + -7x = 0 -27 + 3x = 54 + 0 -27 + 3x = 54 Add '27' to each side of the equation. -27 + 27 + 3x = 54 + 27 Combine like terms: -27 + 27 = 0 0 + 3x = 54 + 27 3x = 54 + 27 Combine like terms: 54 + 27 = 81 3x = 81 Divide each side by '3'. x = 27 Simplifying x = 27
| (14-y)=12 | | 2x+1=3x-8 | | 8(3x-5)=38 | | 3(6-d)=18 | | 1.2x+3.7=2.2-4.5 | | 6h-7=-73 | | -1r=6 | | x^2y^2=2x | | ln(x)+5=0 | | (5)(-10)= | | x-8y=-11 | | 3x+4x+5x=90 | | 333x-54=7 | | 55x+5y=25 | | (13)(0)(-16)= | | 2(7-7x)=2x+4 | | 4p^2+7p-2=0 | | 2(7-7x)=2x-4 | | 114-2x=34x+18 | | p+6/3=4p+3/8 | | (-7)(4)(3)= | | 1/3(p-3)=114 | | (-5)(2)(-3)= | | 2(x-1)-4=-2 | | 6x^2+x^2-24x-4=0 | | 2x-1-4=-2 | | 2p+4q=12 | | 3x^2+12x=1 | | 2g^2-35g+17= | | 4x^2-16x+7= | | m^2-7m-18= | | 8m^3+14m^2-20= |